(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Considerazioni introduttive - 2. Le radici della disciplina canonica sulle reliquie e la fenomenologia dei furta sacra - 3. Il periodo aureo della legislazione in tema di reliquie: la riforma di Urbano VIII e la sistematizzazione di Benedetto XIV - 4. Il Codex del 1917: un supporto moderno per una normativa antica - 5. Il can. 1190 del Codice giovanneo-paolino: un frammento superstite di una esigua storia giuridica - 6. Dedicatio altaris: a cavallo tra obbligo e raccomandazione - 7. Autenticità e conservazione delle reliquie: la competenza della Congregazione delle cause dei santi - 8. La competenza della Congregazione per il culto divino e la disciplina dei sacramenti sul legittimo regime cultuale - 9. Le peculiarità proprie del Codex Canonum Ecclesiarum Orientalium - 10. Il Catechismo della Chiesa cattolica e le indicazioni della CEI: disposizioni a completamento del quadro normativo - 11. È lecito parlare di compravendita di reliquie all’interno dell’ordinamento ecclesiale? - 12. La nuova primavera del commercio delle reliquie: profili civilistici - 13. Riflessioni sull’applicazione della legge penale: provocazioni e nuovi orizzonti d’esplorazione. Fragments between heaven and earth. The discipline of relics between canon law and the secular one ABSTRACT: The aim of this study is to give an account of relics and in order to achieve it the paper examines three different perspectives. The first section charts the origin of the reliquary cult through an historical and systematic reconstruction, starting from the early Christianity until the 1917 Code of canon law. The second segment looks in more detail at the demanding objective to examine Church’s law in force on relics as well as relics worship. The normative to be analysed is contained in many different legislative sources, which have been object of little interest in terms of canonistic doctrine. The third and last section of this study points out the rising of the market of relics in our contemporary society. In particular, this point will be analysed through the eyes of the jurist who deals with religious matters, taking into account the complexity that links the canonical system to the national one, underlying the significant difficulties that the secular judiciary has to face when it comes to express themselves about subjects of “different order”.